POLLEN, PHYTOLITH, MACROFLORAL, AND PARASITE ANALYSIS OF A PRIVY DEPOSIT AND IDENTIFICATION OF MACROFLORAL REMAINS FROM TRASH DEPOSITS IN A PRIVY/TRASH PIT ON BLOCK 24, LOT 10, SKAGWAY, ALASKA - Scott Cummings, Linda (PaleoResearch Institute); Puseman, Kathryn (PaleoResearch Institute) (the Digital Archaeological Record)
A human coprolite from a privy/trash pit on Block 24, Lot 10 in Skagway, Alaska, was sampled for pollen, phytolith, macrofloral, and parasite remains to determine types of food eaten, possible parasite infestation, and potential trash discarded by a catholic priest or priests during the pits use as a privy. Lot 10 was the site of the resident Roman catholic priests rectory from 1903 to 1933. The privy/trash pit is associated with the rectory. Use of the privy is believed to have occurred from 1903 to sometime between 1908 and 1914. After use of the privy ended, the pit is believed to have been used by Father Philibert J.Turnell, S.J. for trash disposal until the 1920s. Macrofloral remains from the level of trash fill were identified to determine foods that Father Turnell had access to and consumed.